A Possible Approach to Fiscal Rules in Small Islands : Incorporating Natural Disasters and Climate Change - Nakatani, Ryota (IMF Working Papers; Working Paper ;, 2019)
A big challenge for the economic development of small island countries is dealing with external shocks. The Pacific Islands are vulnerable to natural disasters, climate change, commodity price changes, and uncertain donor grants. The question that arises is how should small developing countries formulate a fiscal policy to achieve economic stability and fiscal sustainability when prone to various shocks? We study how natural disasters affect long-term debt dynamics and propose fiscal policy rules that could help insulate the economy from such unexpected shocks. We propose fiscal rules to address these shocks and uncertainties using the example of Papua New Guinea. Our study finds the advantages of expenditure rules, especially a recurrent expenditure rule based on non-resource and non-grant revenue, interdependently determined by government debt and budget balance targets with expected disaster shocks. This paper contributes to the literature and policy dialogue by theoretically analyzing the impact of natural disasters on debt sustainability and proposing fiscal rules against natural disasters and climate changes. Our fiscal policy framework is practically applicable for many developing countries facing increasing frequency and impact of natural disasters and climate change. Our rules-based fiscal framework is crucial for sustainable and countercyclical macroeconomic policies to build resilience against devastating natural hazards.